Fostering Ethical Decision-Making Skills in Pharmaceutical Education: Vital for Future Pharmacists - Leelavati, Thota Suguna; Madhavi, Sripathi; Aminabee, Shaik (Indian Journal of Pharmaceutical Education and Research, 2025)
Ethical decision-making is a fundamental aspect of pharmacy practice, as pharmacists often face complex moral dilemmas while providing patient care and dispensing medications. The incorporation of ethical training in pharmaceutical curricula is crucial to equip future pharmacists with the necessary skills to navigate these challenging situations responsibly. This paper explores the importance of integrating ethical decision-making training in pharmacy education and discusses the potential benefits and challenges associated with its implementation. Various teaching approaches, case-based learning, and simulation-based methods are examined for their effectiveness in fostering ethical competency among pharmacy students. Additionally, the paper highlights the role of faculty development programs and institutional support in successfully incorporating ethical training into pharmacy curricula. Recommendations for developing a comprehensive ethical decision-making curriculum and its potential impact on pharmacy practice are presented, emphasizing the significance of nurturing morally competent and responsible pharmacists.
Keywords: Ethical decision-making; Pharmacy education; Ethical training; Curriculum development; Patient care; Pharmacy practice.